How much of cross-country income variation is explained by health? - Gauri Kartini Shastry; David N. Weil (Brown University, Department of Economics, 2003)
We use development accounting techniques to assess the contribution of health to differences in income per capita among countries. Rather than rely on regressions in aggregate data, we build up estimates of the effect of health starting from microeconomic data. We examine both a particular condition, anemia, and a proxy for general health, the adult survival rate. We find that differences in anemia explain 1.3% of the log variance of income per capita, and that differences in adult survival explain 19% of the log variance of income per capita. The latter figure is almost one-third of the variation in output that is left unexplained by other measures of factor accumulation.
Keywords: 330; Einkommensverteilung; Sozialprodukt; Gesundheit; Welt